Why Teacher Job Satisfaction Matters: Strengthening Head Teachers’ Transformational Leadership in Sustainable Development Education - Marni, Marni; Abdullah, Khairul Hafezad; Faiz Mohd Yaakob, Mohd Faiz Mohd; Fauzee, Mohd Sofian Omar; Jamil, Syahira Fairishmar; Ahmad Abdelaziz Al-Zu'bi, Mohamad; Daljit Singh Gurbaksh, (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Achieving Cluster School of Excellence (CSE) status relies on teachers’ job satisfaction. This facet is crucial in driving the school towards its goals. This research employs a mixed-methods approach, incorporating both quantitative and qualitative measures. The quantitative phase includes 177 teachers from six CSE primary schools in Kota Setar, Kedah, Malaysia. In contrast, the qualitative phase involves in-depth interviews with 20 teachers. In the quantitative phase, this study employed two questionnaire instruments, the Multifactor Leadership Questionnaire (MLQ) and the Job Satisfaction Index (JSI). These instruments were utilised to assess headteachers’ transformational leadership level and job satisfaction in school. Within the qualitative phase, the researchers employed a semi-structured questionnaire to categorise positive and negative ideas regarding the four aspects of transformational leadership. The quantitative results indicated that four transformational leadership dimensions significantly relate to teacher job satisfaction explicitly: charisma (idealised influence), intellectual stimulation, individual consideration, and inspirational motivation. The qualitative results based on content analysis showed the frequency of responses for each dimension as follows: charisma (affirmative = 120, negative = 15), intellectual stimulation (affirmative = 80, negative = 15), individual consideration (affirmative = 70, negative = 16), and inspirational Motivation (affirmative = 40, negative = 16). The study concludes that the critical role of transformational leadership in promoting job satisfaction among teachers is crucial for achieving CSE status. The substantial correlations between teacher job satisfaction and the transformational leadership dimensions emphasise the significance of effective leadership in the school ecosystem. As a result, improving transformational leadership practices within schools can result in a more motivated and contented teaching workforce, contributing to the school’s overall success.